Vacuum-assisted excision: a safe minimally invasive option for benign phyllodes tumor diagnosis and treatment—a systematic review and meta-analysis - Gil, Maria Luísa Braga Vieira; Coelho, Bertha Andrade; Couto, Henrique Lima; Silva, Henrique Moraes Salvador; Pessoa, Eduardo Carvalho [UNESP]; Sharma, Nisha; Mann, Ritse; McIntosh, Stuart A.; Diniz, Paulo Henrique Costa; Cantidio, Farley Soares; Gil, Gabriel Oliveira Bernardes; Salvador, Anna Dias; et al. (Frontiers, 2024)
Synopsis: This is a systematic review and meta-analysis comparing surgical excision with percutaneous ultrasound-guided vacuum-assisted excision (US-VAE) for the treatment of benign phyllodes tumor (PT) using local recurrence (LR) as the endpoint. Objective: To determine the frequency of local recurrence (LR) of benign phyllodes tumor (PT) after ultrasound-guided vacuum-assisted excision (US-VAE) compared to the frequency of LR after surgical excision. Method: A systematic review and meta-analysis [following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard] was conducted by comparing LR in women older than 18 years treated for benign PT by US-VAE compared with local surgical excision with at least 12 months of follow-up. Studies were retrieved from PubMed, Scopus, Web of Science, and Embase. The pooled effect measure used was the odds ratio (OR) of recurrence. Results: Five comparative prospective or retrospective observational studies published between January 1, 1992, and January 10, 2022, comparing surgical excision with percutaneous US-VAE for LR of benign PT met the selection criteria. Four were retrospective observational cohorts, and one was a prospective observational cohort. A total of 778 women were followed up. Of them, 439 (56.4%) underwent local surgical excision, and 339 (43.6%) patients had US-VAE. The median age of patients in the five studies ranged from 33.7 to 39 years; the median size ranged from 1.5 cm to 3.0 cm, and the median follow-up ranged from 12 months to 46.6 months. The needle gauge ranged from 7G to 11G. LR rates were not statically significant between US-VAE and surgical excision (41 of 339 versus 34 of 439; OR 1.3; p = 0.29). Conclusion: This meta-analysis suggests that using US-VAE for the removal of benign PT does not increase local regional recurrence and is a safe minimally invasive therapeutic option. Systematic review registration: https://www.crd.york.ac.uk/prospero/, identifier CRD42022309782.
Keywords: local recurrence; meta-analysis; phyllodes tumor; review; vacuum-assisted biopsy; vacuum-assisted excision